Ludzie czy zwierzęta? Przodkowie w mitach Uluru u Pitjantjatjara = Humans or animals? Ancestors in Pitjantjatjara myths of Uluru - Szyjewski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Myths focusing on the Uluru (Ayers Rock) are closely correlated with the characteristic elements of its shape. This allows us to formulate a number of proposals concerning the perception of Aboriginal mythical ancestors, especially their animal versus human characteristics. In contrast to the totally hybrid status of demonic beings (mamu), such as Kurpany, ancestors reveal their ambigous nature rather seldom.
Keywords: mit; Aborygeni australijscy; Pitjantjatjara; inicjacja; Uluru; Ayers Rock; struktura społeczna; transformacja; myth; Australian Aborigines; initiation; social structure; transformation